Student Knowledge about Sexual Harassment Prevention in Vocational High Schools - Salsabila, Putri; Karneli, Yeni (International Journal of Applied Counseling and Social Sciences, 2024)
This research is motivated by the rampant cases of sexual harassment in adolescents, including in the school environment. Because adolescents are a vulnerable group and are still vulnerable to sexual things due to various factors, including a lack of knowledge about how to protect themselves. The study aims to describe the knowledge of vocational school students about sexual harassment prevention, using a quantitative method with a descriptive approach in 299 students of SMKN 2 Pariaman, who were randomly selected. Data were collected through a questionnaire that had been tested for validity with the Pearson correlation formula (0.312) and reliability test with the Cronbach alpha formula (0.878). The results showed that 68.76% of students had moderate knowledge in prevention in the primary prevention aspect, 70.71% in the prevention of sexual harassment in the secondary aspect, and 69.89% in the prevention of sexual harassment in the tertiary prevention aspect. This means that students have sufficient knowledge about preventing and dealing with sexual harassment before, during, and after the incident. This study recommends the role of counselors as an important educational resource in increasing students' knowledge about sexual harassment.